HEDONISM AS A MECHANISM OF RESISTANCE TO A TOTALITARIAN SYSTEM (ON THE MATERIAL OF UKRAINIAN PROSE OF THE LATE 20 — EARLY 21 CENTURIES) - Telets, Yurii (Літературний процес: методологія, імена, тенденції, 2019)
DOI: 10.28925/2412-2475.2019.1415 The article analyses the dichotomy of the Imperial and Post-Imperial experience outlined in the Ukrainian postcolonial prose of the late 20 – early 21 centuries from the point of view of hedonism as a specific mechanism of resistance to the totalitarian system. The features of Ukrainian-Russian relations in the system of «colony — Empire» are defined and the specifics of hedonistic worldview through the transformation of behavioral tactics of the heroes of modern Ukrainian prose are determined. On the basis of historical-literary and comparative methods of text analysis, the markers of the behavior of hedonic characters as a reaction to the prevailing regime in reality are proposed. As a result of the study, it is determined that the ambiguity and inconsistency of the Ukrainian-Russian relations in the system of «colony — Empire» determine the specificity of hedonistic worldview and behavioral tactics of the heroes of modern Ukrainian prose. In connection with the change of the political system and the partial deconstruction of the Imperial discourse, the characters are experiencing a crisis that becomes a catalyst for permanent escape from the oppressive reality and its inhibiting factors. The hero of Ukrainian postcolonial prose is not always able to realize his own nationality and, acting as a latent carrier of dualistic self-identification, avoids the bleak of physical and mental aspects thanks to escapism. The desired escape from reality, exit into unconscious space are possible only through the avoidance of spiritual suffering and obtaining non prolonged, but constant pleasure from alcoholic beverages and drugs.